Estimacion Del Potencial De Captura De Agua Atmosferica En Guásimas, Sonora - Bautista-Olivas, Ana Laura; Bautista, Fidencio Cruz (European Scientific Journal, ESJ, 2018)
This paper focuses on estimating the potential of the atmospheric conditions in the locality of Guásimas Sonora for the capture of atmospheric water. To achieve this goal, an automated meteorological station was installed to record the ambient temperature, relative humidity, wind speed, and precipitation at the study site. According to the results obtained, the potential of the atmospheric conditions for the capture of water in the locality of Guásimas, in general, is medium. It presents a period of 20 to 30 days a year to capture atmospheric water with passive collectors and between 105 and 130 days during the year for the condensation of atmospheric water with active collectors.